The Myth of Eliminating AEG: Revisiting the Literature - Nael Sayedahmed; Adnan Tahir; Nidhi Oswal (RIRAI Publisher, 2022)
During the past few years, there have been extensive research that investigated the Audit Expectation Gap (AEG) from different perspectives. One of the most common areas of discussion was the importance of narrowing down the gap and harmonizing different opinions of involved parties in this problem. The current research starts by explaining AEG, its reasons, its impacts on both auditors and users of financial statements, and finally how the gap could be eliminated. This is done through extensive review of literature about the topic in both developed and developing countries, where a theoretical construct is presented for AEG and most effective procedures for elimination of AEG are later presented and for different environments.